Clinical features of the head and neck mucosal melanoma. А review - A. V. Ignatova (Opuholi Golovy i Šei, 2016)
Melanoma is an aggressive and rare neoplasm of melanocytic origin. Mucosal melanomas of the head and neck account for 1 % of neoplasms, 0,2–8,0 4 % of all melanomas and over 50 % of all mucosal melanomas. To date, in Russian and foreign literature only few retrospective series and case reports have been reported on mucosal melanoma. Despite melanoma’s common histological origin, head and neck mucosal melanoma presentation has some specific features due to its anatomical localization and poor clinical outcomes compared with those of cutaneous melanomas. Mucosal melanoma has a high metastatic potential. Five-year overall survival does not exceed 30 %. Advances in understanding of the clinical presentation can be used for prediction of behaviour and prognosis of this disease. We considered and analised articles devoted to clinical features of head and neck mucosal melanoma according to its localization.